ANALSIS PENAGIHAN PAJAK DENGAN SURAT PAKSA PADA KANTOR PELAYANAN PAJAK PRATAMA MANADO - Pontoh, Melva Karla Yece; Tinangon, Jantje J.; Sabijono, Harijanto (GOING CONCERN : JURNAL RISET AKUNTANSI, 2014)
Tax is an important element in APBN because tax as the largest thing  of national fund.  In fact there are tax payers in low obedience so they don’t pay and make report giving them by tax penalty, that is the basic element for Tax Billing and one of them is Tax Billing by Enforcement Letter.  According to my research I use Descriptive Methode to analize data.  According to my research I can conclude that Tax Billing by Enforcement Letter at Kantor Pelayanan Pajak Pratama Manado has been run according to the procedure.  That also give a good effect in order to undertake the Arrears Disbursement.  One of the good result do assessable is make them wary s for future the Assessable will be more obedient to fulfill they Tax Responsibility.  Suggestions can be put forward for the further course of a study should be conducted in-depth research to add to the reference library.